2019
DOI: 10.1136/neurintsurg-2019-015330
|View full text |Cite
|
Sign up to set email alerts
|

Successful reperfusion, rather than number of passes, predicts clinical outcome after mechanical thrombectomy

Abstract: IntroductionFor patients undergoing mechanical thrombectomy, numerous (>3) thrombectomy passes may be harmful. However, non-recanalization leads to poor outcomes. For patients requiring multiple thrombectomy passes to achieve reperfusion, it remains unclear if the risk/benefit ratio favors recanalization.ObjectiveTo test the hypothesis that the benefits afforded by successful reperfusion outweigh the risk conveyed by the numerous passes required.MethodsWe retrospectively reviewed prospectively collected dat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
36
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 61 publications
(39 citation statements)
references
References 14 publications
3
36
0
Order By: Relevance
“…Similar results were reported by Tonetti et al [10], who showed, that patients who achieve successful reperfusion after ≥4 passes have significantly better rates of functional outcomes than those who do not achieve reperfusion. Furthermore, no patient with TICI 2a or worse reperfusion achieved favorable outcome.…”
supporting
confidence: 89%
“…Similar results were reported by Tonetti et al [10], who showed, that patients who achieve successful reperfusion after ≥4 passes have significantly better rates of functional outcomes than those who do not achieve reperfusion. Furthermore, no patient with TICI 2a or worse reperfusion achieved favorable outcome.…”
supporting
confidence: 89%
“…[1][2][3] Although the chances for a clinical benefit are optimal if complete reperfusion is attained after the first pass, 4 5 there is a growing body of evidence suggesting that an effect of improved reperfusion is still tangible after multiple attempts and prolonged procedure time. [6][7][8] Despite recent technical advances, failed reperfusion (Thrombolysis in Cerebral Infarction (TICI) 0/1) is the final result of MT in every 10th patient, [9][10][11] and most patients treated successfully do not reach complete reperfusion (TICI 3). 12 13 Treatment options in these scenarios are distal MT of thrombus fragments, 7 14 bailout stenting 15 or administration of intra-arterial (IA) fibrinolytics.…”
Section: Introductionmentioning
confidence: 99%
“…In the study of Nogueira et al, Despite successful recanalization rates, good clinical results evaluated with the mRS score ≤ 2 were obtained in only half of the patients (21). Some authors have identified a lot of clinic factors that influence poor outcomes in patients with AIS treated with MT (22,23). In some studies, the association of laboratory parameters with poor functional results was evaluated (24, 265).…”
Section: Discussionmentioning
confidence: 99%